2022
DOI: 10.3389/fphar.2022.961788
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and berberine co-loaded liposomes for anti-hepatocellular carcinoma therapy by blocking the cross-talk between hepatic stellate cells and tumor cells

Abstract: Cancer-associated fibroblasts (CAFs) are a major component of the tumor microenvironment (TME). In hepatocellular carcinoma (HCC), quiescent hepatic stellate cells (HSCs) could be activated to become CAFs, which play a critical role in tumor progression and drug resistance. Therefore, recent efforts have been focused on combining anti-HSC and pro-apoptotic activities to improve anti-tumor efficacy of drugs. In this study, glycyrrhetinic acid and hyaluronic acid–modified liposomes (GA-HA-Lip) were prepared for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In particular, Guo and his partner found that GA could inhibit human telomerase reverse transcriptase gene expression in human hepatoma SMMC-7721 cells, resulting in the inhibition of HCC development ( Nie et al., 2009 ). Another study found that GA could induce antiproliferation in HCC cell lines ( Wu et al., 2022 ). Because HBV is closely related to HCC, we wanted to explore whether GA plays an essential role in HBV.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Guo and his partner found that GA could inhibit human telomerase reverse transcriptase gene expression in human hepatoma SMMC-7721 cells, resulting in the inhibition of HCC development ( Nie et al., 2009 ). Another study found that GA could induce antiproliferation in HCC cell lines ( Wu et al., 2022 ). Because HBV is closely related to HCC, we wanted to explore whether GA plays an essential role in HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Both curcumin and berberine have been loaded on liposomes and they show high accumulation at tumor tissue. This co-delivery stimulates apoptosis and suppresses proliferation, and one of its benefits is disrupting the interaction of cancer cells and hepatic stellate cells in HCC therapy [110] .…”
Section: Liposomes and Delivery Systems In Hepatocellular Carcinomamentioning
confidence: 99%
“…Such drug-loaded liposomes showed uptake by HCC cells and cancer-associatd fibroblasts that suppressed tumorigenesis in vitro and in vivo, and disrupted the invasion [217] . In another effort, GA/HA-functionalized liposomes were utilized to co-deliver berberine and curcumin that were able to stimulate apoptosis in tumor cells and impair their proliferation [110] . The HCC cells demonstrate overexpression of folate receptor to bring up folate for their proliferation.…”
Section: Functionalized Liposomesmentioning
confidence: 99%
“…Finally, there exists only one study for each of the three remaining flavonoids recently enclosed in HA-containing nanosystems (i.e., the flavonol kaempherol, the flavanone The nanoformulations designed for the targeted delivery of phenolic compounds (PheCs) to cancer cells are, in most cases, polymeric nanoparticles (NPs) having hyaluronic acid (HA) among the constituent polymers or NPs decorated at the surface with HA alone or accompanied by additional targeting ligands. Among the additional targeting ligands used, there are: fucoidan, that functions as a ligand for P-selectin and helps the nanosystems to be internalized in cancer cells [42,44,46]; EGF Receptor-Targeted Peptide (GE11) for binding to EGFR overexpressed in prostate cancer [49]; folic acid and biotin functioning as ligands for the respective receptors, both overexpressed in cancer cells [67]; mannose for the binding to the CD206 receptor for specifically targeting the tumor-associated macrophages (TAMs) [68]; glycyrrhetinic acid (GA) that binds to the specific receptor overexpressed in hepatocarcinoma cells and in activated hepatic stellate cells (HSCs) [73]; riboflavin [74]. Besides HA, other bioactive constituents of the nanoformulation shells are: the bisphosphonate alendronate, able to specifically target osteosarcoma cells [69]; D-alpha-tocopheryl polyethylene glycol 1000 succinate (TPGS), able to inhibit P-gp efflux pumps, thus overcoming multidrug resistance (MDR) in cancer [40].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%